The Wild West Turns East: Audience,Fugitive Mail: The Deliverance of Henry “Box” Brown and Antebellum Postal Politics - Robbins, Hollis (American Studies, 2009)
“Fugitive Mail: The Deliverance of Henry “Box” Brown and Antebellum Postal Politics” reconsiders the publication, reception, and revival of The Narrative of Henry “Box” Brown (1849, 1851) the story of a slave who successfully mailed himself from Richmond, Virginia to Philadelphia, in the context of the postal system’s role in the abolitionist movement. Nearly all of the scholarly treatments of Brown’s narrative in the last decade emphasize and celebrate the shipment of “Box” Brown as a metaphorical deliverance, a Middle Passage; few Brown scholars explore the role of Adams Express, the private mail service that delivered Brown to freedom in 27 hours. “Fugitive Mail” explores the postal consciousness of Brown and the abolitionist movement to argue that Brown’s narrative is far more important as a first-person account of the success of new express mail services in mid-nineteenth-century America than as a traditional escape narrative.